Unravelling the Population Genetic Dynamics of the Ivory Snail (Babylonia areolata) in Vietnam: Guiding Sustainable Aquaculture Development - Sang Van Vu; Angkasa Putra; Sarifah Aini; Imon Abedin; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Thanh Tat Le; Hoang Huy Nguyen; Hien Van Doan; In Van Vu; Hyun-Woo Kim; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Biological control of tomato bacterial wilt and apple fire blight using n-docosane, a plant resistance inducer from Streptomyces sp. JCK-8055 - Loan Thi Thanh Nguyen; Ae Ran Park; Chea-Won Oh; Hye-Won Im; Van Hien La; Jin-Cheol Kim (Pesticide Biochemistry and Physiology, 2026)

Mitogenomic Characterization and Phylogenetic Insights of the Ornamental Sail-Fin Molly (Poecilia velifera) in Non-Native Indonesian Waters - Sarifah Aini; Rina; Sinar Pagi Sektiana; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Muhammad Hilman Fu’adil Amin; Won-Kyo Jung; Angkasa Putra; I Nyoman Suyasa; Shantanu Kundu; Hyun-Woo Kim (Biochemical Genetics, 2026)

Integrated hydroprocessing and microbial biotransformation of coconut oil to α,ω-diacids - Bashu Dev Pardhe; Il-Ho Choi; Chang Hoon Lee; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Hwabong Jeong; Jongbeom Park; Kyung Taek Heo; et al. (Bioresource Technology, 2025)

Development of polymorphic simple sequence repeat markers for assessing genetic diversity and cross-species transferability in Polygonatum species - Raveendar Sebastin; Ki Hyun Kim; Hye Ran Shin; Yumi Kim; Sewon Oh; Ick Hyun Jo; Ju-Kyung Yu; Yi Lee; Yoon-Sup So; Jong-Wook Chung (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Effect of pesticide formulation on initial residue levels in crops: a meta-analysis approach - So-Hee Kim; Hye-Ran Eun; Min-Seok Kim; Hyun-Woo Kim; Ji Won Lee; Hyun Ho Noh (Environmental Pollution, 2025)

Physicochemical characterization and in vivo assessment of novel apixaban-loaded polymeric nano-aggregates - Fakhar ud Din; Hye In Lee; Jung Suk Kim; Mi Ran Woo; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Identification and functional analysis of MYB group transcripts in formation and development of rose prickle - Ka Youn Lee; Yae Jin Kim; Chang Ho Ahn; Kyoung Ran Do; Youn Jung Choi; Jae A. Jung; O Hyeon Kwon; Hye Ryun An; So Hyeon Lim; Su Young Lee (Euphytica, 2025)

Development of a novel apixaban-loaded solid self-emulsifying drug delivery system for oral administration: physicochemical characterization and pharmacokinetics in rats - Hye In Lee; Mi Ran Woo; Fakhar ud Din; Jung Suk Kim; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Effects of heat stress on growth performance, physiological responses, and carcass traits in broilers - Hye Ran Kim; Pilnam Seong; Kuk-Hwan Seol; Jong-Eun Park; Hana Kim; Woncheoul Park; Jin Ho Cho; Sung Dae Lee (Journal of Thermal Biology, 2025)

Deciphering the links: Fragmented polystyrene as a driver of skin inflammation - Gyeong Bae Song; Jisoo Nam; Sangmin Ji; Gijeong Woo; Soojeong Park; Bokyung Kim; Jeein Hong; Myung Gil Choi; Seokheon Kim; Chaerin Lee; Wonchul Lim; Sangwoon Yoon; et al. (Journal of Hazardous Materials, 2024)

Nitric acid modified powdered activated carbon for simultaneous adsorption of lead and phenol in aqueous solution - Hyun-Kyung Kim; So-Jeong Kim; Hye-Ran Kim; Jae-Woo Park (Journal of Environmental Chemical Engineering, 2024)

Characterization and solubility measurement of synthetic uranophane and sklodowskite under oxic groundwater conditions - Wansik Cha; Junghwan Park; Euo Chang Jung; Hye Ran Noh; Hee-Kyung Kim; Hye-Ryun Cho (Applied Geochemistry, 2024)

Safety of applying influenza-antigen-coated microneedles to rat skin and the antigen specific immune response in vivo - Taek-Seon Yun; Bomin Song; Yu-Rim Hwang; Minki Jin; Hyeseung Seonwoo; Donki Kim; Hye Won Kim; Byeong Cheol Kim; Daekyung Kim; Boyeong Park; Jeong Yeon Kang; Seung-Ki Baek; et al. (Journal of Pharmaceutical Investigation, 2024)

Effect of seven days heat stress on feed and water intake, milk characteristics, blood parameters, physiological indicators, and gene expression in Holstein dairy cows - Jang-Hoon Jo; Jalil Ghassemi Nejad; Hye-Ran Kim; Hong-Gu Lee (Journal of Thermal Biology, 2024)

Lysolecithin-fatty acid liposomes as novel antibacterial agents to suppress the growth of periodontal Porphyromonas gingivalis - Jeong-Hoo Lee; Hyo-Ran Lee; Yeeun Park; Hye-Seong Lee; Jiyoung Hwang; Gyuwhan Lee; Hye-Sung Kim; Inseong Hwang; Jin-Byung Park (Food Bioscience, 2024)

Development of polymorphic simple sequence repeat markers in Agastache rugosa and their application in genetic evaluation and cross-taxon transferability of Agastache species - Hye Ran Shin; Ick Hyun Jo; Raveendar Sebastin; Jinsu Gil; Gi Yeong Kim; Suyun Moon; Hyun-Seung Park; Sewon Oh; Jong Won Han; Kyung Ho Ma; Yi Lee; Daeil Kim; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Relationship between PM1.0 and PM2.5 in urban and background areas of Republic of Korea - Sujin Kwon; Soo Ran Won; Hyung Bae Lim; Sung Chul Hong; Yong Mi Lee; Ji Yun Jung; Sung-Deuk Choi; Sang-Jin Lee; Seungmee Oh; Ju Young Kim; Yong Pyo Kim; Hye Jung Shin; et al. (Atmospheric Pollution Research, 2023)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Correction to: A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2022)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.

A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2021)

Ovalbumin and cholera toxin delivery to buccal mucus for immunization using microneedles and comparison of immunological response to transmucosal delivery - Yu-Jeong Oh; Hye-Ran Cha; Su Jin Hwang; Dae-Sung Kim; Yu-Ji Choi; Yun-Seo Kim; Yu-Ra Shin; Thuy Trang Nguyen; Seong-O Choi; Jae Myun Lee; Jung-Hwan Park (Drug Delivery and Translational Research, 2021)

Novel diamide resistance-linked mutation in Korean Spodoptera exigua and a LAMP assay based on a mutation-associated intronic InDel - Juil Kim; Hwa Yeun Nam; Min Kwon; Ji Hye Choi; Sun Ran Cho; Gil-Hah Kim (Journal of Pest Science, 2021)

Emergence of vancomycin-resistant Enterococcus faecium ST1421 lacking the pstS gene in Korea - Hye Mee Kim; Doo Ryeon Chung; Sun Young Cho; Kyungmin Huh; Cheol-In Kang; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Effect of Combined Exposure to EDTA and Zinc Pyrithione on Pyrithione Absorption in Rats - Dong Sik Jung; Guk Hwa Jung; Eun Ho Lee; Hye Ran Park; Ju Hwan Kim; Kyu-Bong Kim; Hak Rim Kim; Hyung Gun Kim (Toxicological Research, 2019)

Metformin Inhibits the Development of l-DOPA-Induced Dyskinesia in a Murine Model of Parkinson’s Disease - Young-Kyoung Ryu; Hye-Yeon Park; Jun Go; Dong-Hee Choi; Yong-Hoon Kim; Jung Hwan Hwang; Jung-Ran Noh; Tae Geol Lee; Chul-Ho Lee; Kyoung-Shim Kim (Molecular Neurobiology, 2018)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Ethnobotany of the wild edible plants gathered in Ulleung Island, South Korea - Homervergel G. Ong; Jae-Min Chung; Hye-Ran Jeong; Young-Dong Kim; Kyung Choi; Chang-Ho Shin; You-Mi Lee (Genetic Resources and Crop Evolution, 2016)

Endosulfan induces COX-2 expression via NADPH oxidase and the ROS, MAPK, and Akt pathways - Hyung Gyun Kim; Young Ran Kim; Jin Hee Park; Tilak Khanal; Jae Ho Choi; Minh Truong Do; Sun Woo Jin; Eun Hee Han; Young Ho Chung; Hye Gwang Jeong (Archives of Toxicology, 2015)

Mercury contamination and exposure assessment of fishery products in Korea - Hye-Ran Yang; Na-Young Kim; Lae-Hong Hwang; Ju-Sung Park; Jung-Hun Kim (Food Additives & Contaminants Part B-Surveillance, 2015)

Role of vacuolating cytotoxin VacA and cytotoxin-associated antigen CagA of Helicobacter pylori in the progression of gastric cancer - Mi-Ran Ki; Meeyul Hwang; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Myeong-Mi Lee; Soo-Eun Sung; Sang-Hyeob Kim; Hye Seung Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Thymol from Thymus quinquecostatus Celak. protects against tert-butyl hydroperoxide-induced oxidative stress in Chang cells - Yon-Suk Kim; Jin-Woo Hwang; Seo-Hee Kang; Ee-Hwa Kim; You-Jin Jeon; Jae-Hyun Jeong; Hye-Ran Kim; Sang-Ho Moon; Byong-Tae Jeon; Pyo-Jam Park (Journal of Natural Medicines, 2014)

Molecular characterization of a cysteine proteinase inhibitor, PgCPI, from Panax ginseng C. A. Meyer - Dae-Young Jung; Ok Ran Lee; Yu-Jin Kim; Jung-Hye Lee; Rama Krishna Pulla; Gayathri Sathiyaraj; Ju-Sun Shim; Deok-Chun Yang (Acta Physiologiae Plantarum, 2010)

Comparative studies of skeletal muscle proteome and transcriptome profilings between pig breeds - Nam-Kuk Kim; Hye-Ran Park; Hwi-Cheul Lee; Duhak Yoon; Eun-Suk Son; Yeun-Song Kim; Se-Ra Kim; Oun-Hyun Kim; Chang-Soo Lee (Mammalian Genome, 2010)

An atypical soybean leucine-rich repeat receptor-like kinase, GmLRK1, may be involved in the regulation of cell elongation - Sunghan Kim; Su-Jin Kim; Yun-Jeong Shin; Ji-Hye Kang; Mi-Ran Kim; Kyoung Hee Nam; Myeong-Sok Lee; Suk-Ha Lee; Yul-Ho Kim; Soon-Kwan Hong; Desh Pal S. Verma; Jong-Yoon Chun; et al. (Planta, 2009)

Development of a BAC library for yellow-poplar (Liriodendron tulipifera) and the identification of genes associated with flower development and lignin biosynthesis - Haiying Liang; Eric G. Fang; Jeffrey P. Tomkins; Meizhong Luo; David Kudrna; Hye Ran Kim; K. Arumuganathan; Shaying Zhao; James Leebens-Mack; Scott E. Schlarbaum; Jo Ann Banks; Claude W. dePamphilis; et al. (Tree Genetics & Genomes, 2007)

Candidate gene database and transcript map for peach, a model species for fruit trees - Renate Horn; Anne-Claire Lecouls; Ann Callahan; Abhaya Dandekar; Lilibeth Garay; Per McCord; Werner Howad; Helen Chan; Ignazio Verde; Doreen Main; Sook Jung; Laura Georgi; et al. (Theoretical and Applied Genetics, 2005)

CHRK1, a chitinase-related receptor-like kinase, plays a role in plant development and cytokinin homeostasis in tobacco - Jeong Hee Lee; Kentaro Takei; Hitoshi Sakakibara; Hye Sun Cho; Do Myung Kim; Youn Sung Kim; Sung Ran Min; Woo Taek Kim; Dae Young Sohn; Yong Pyo Lim; Hyun-Sook Pai (Plant Molecular Biology, 2003)